Glucose Transporter 3 Potentiates Degranulation and Is Required for Platelet Activation. Issue 9 (September 2017) - Fidler, Trevor P.; Middleton, Elizabeth A.; Rowley, Jesse W.; Boudreau, Luc H.; Campbell, Robert A.; Souvenir, Rhonda; Funari, Trevor; Tessandier, Nicolas; Boilard, Eric; Weyrich, Andrew S.; Abel, E. Dale
Abstract : Objective—: On activation, platelets increase glucose uptake, glycolysis, and glucose oxidation and consume stored glycogen. This correlation between glucose metabolism and platelet function is not well understood and even less is known about the role of glucose metabolism on platelet function in vivo. For glucose to enter a cell, it must be transported through glucose transporters. Here we evaluate the contribution of GLUT3 (glucose transporter 3) to platelet function to better understand glucose metabolism in platelets. Approach and Results—: Platelet-specific knockout of GLUT3 was generated by crossing mice harboring GLUT3 floxed allele to a PF4 (platelet factor 4)-driven Cre recombinase. In platelets, GLUT3 is localized primarily on α-granule membranes and under basal conditions facilitates glucose uptake into α-granules to be used for glycolysis. After activation, platelets degranulate and GLUT3 translocates to the plasma membrane, which is responsible for activation-mediated increased glucose uptake. In vivo, loss of GLUT3 in platelets increased survival in a collagen/epinephrine model of pulmonary embolism, and in a K/BxN model of autoimmune inflammatory disease, platelet-specific GLUT3 knockout mice display decreased disease progression. Mechanistically, loss of GLUT3 decreased platelet degranulation, spreading, and clot retraction. Decreased α-granule degranulation is due in part to an impaired ability of GLUT3 to potentiate exocytosis. Conclusions—: GLUT3-mediated glucose utilization and glycogenolysis in platelets promotes α-granule release, platelet activation, and postactivation functions. Abstract : Supplemental Digital Content is available in the text.